Dr. A.P.J. Abdul Kalam : A true representative of humankind - Sharma , Neeta Bora; Bisht, Rajendra Prasad (New Delhi Anamika Publishers, 2025)
Dr. A.P.J. Abdul Kalam: A True Representative of Humankind is a unique composition on the life, ideology and achievements of one of the great scientist of India and former President Dr. A.P.J. Abdul Kalam. The Book covers whole life span of Dr. Kalam, from early Childhood struggle to tense movements of scientific achievement, from early failure in career to the crest of popularity, from the close and small environment science labs to the infinite platform of public life, from concrete inventions of science and discovery to abstract statesmanship of politics. The book articulates broadly the Ideology as well as legacy of Dr. Kalam in sector of scientific development and also in the sphere of political arena. The book is full of the life events of Dr Kalam, it gives full and complete documentary of a great personality of modern India. Problems he faced, struggle against the fate, decision he took and achievements he gained are beautifully embellished in the book. The book is able to give readers a new and holistic insight of the ideology and Personality of a great scientist, inventor and leader of post modern India.
Keywords: A. P. J. Abdul Kalam; President of India; Social Welfare